Strategies to Optimize the Efficacy of Anthelmintic Drugs in Ruminants - Lanusse, Carlos Edmundo (2018)
Anthelmintic resistance in human and animal pathogenic helminths has been spreading in prevalence and severity. Multidrug resistance is a widespread problem in livestock animals. The use of available pharmacology-based information is critical to the design of successful future approaches for parasite control. Relevant scientific work supporting the main strategies to optimize anthelmintic therapy in ruminants under the current drug-resistance scenario is described here. We emphasize the need for further integrated pharmaco-parasitological knowledge to extend the lifespan of both traditional and novel anthelmintic compounds, and to progress in the identification of complementary/alternative measures of parasite control in livestock animals.